Serological evaluation of the effectiveness of reactive focal mass drug administration and reactive vector control to reduce malaria transmission in Zambezi Region, Namibia: Results from a secondary analysis of a cluster randomised trial. (February 2022) - Wu, Lindsey; Hsiang, Michelle S.; Prach, Lisa M.; Schrubbe, Leah; Ntuku, Henry; Dufour, Mi-Suk Kang; Whittemore, Brooke; Scott, Valerie; Yala, Joy; Roberts, Kathryn W.; Patterson, Catriona; Biggs, Joseph; et al.
Summary: Background: Due to challenges in measuring changes in malaria at low transmission, serology is increasingly being used to complement clinical and parasitological surveillance. Longitudinal studies have shown that serological markers, such as Etramp5.Ag1, can reflect spatio-temporal differences in malaria transmission. However, these markers have yet to be used as endpoints in intervention trials. Methods: Based on data from a 2017 cluster randomised trial conducted in Zambezi Region, Namibia, evaluating the effectiveness of reactive focal mass drug administration (rfMDA) and reactive vector control (RAVC), this study conducted a secondary analysis comparing antibody responses between intervention arms as trial endpoints. Antibody responses were measured on a multiplex immunoassay, using a panel of eight serological markers of Plasmodium falciparum infection - Etramp5.Ag1, GEXP18, HSP40.Ag1, Rh2.2030, EBA175, Pf MSP119, Pf AMA1, and Pf GLURP.R2. Findings: Reductions in sero-prevalence to antigens Etramp.Ag1, Pf MSP119, Rh2.2030, and Pf AMA1 were observed in study arms combining rfMDA and RAVC, but only effects for Etramp5.Ag1 were statistically significant. Etramp5.Ag1 sero-prevalence was significantly lower in all intervention arms. Compared to the reference arms, adjusted prevalence ratio (aPR) for Etramp5.Ag1 was 0.78 (95%CI 0.65 – 0.91, p = 0.0007) in the rfMDA arms and 0.79 (95%CI 0.67 – 0.92, p = 0.001) in the RAVC arms. For the combined rfMDA plus RAVC intervention, aPR was 0.59 (95%CI 0.46 – 0.76, p < 0.0001). Significant reductions were also observed based on continuous antibody responses. Sero-prevalence as an endpoint was found to achieve higher study power (99.9% power to detect a 50% reduction in prevalence) compared to quantitative polymerase chain reaction (qPCR) prevalence (72.9% power to detect a 50% reduction in prevalence). Interpretation: While the observed relative reduction in qPCR prevalence in the study was greater than serology, the use of serological endpoints to evaluate trial outcomes measured effect size with improved precision and study power. Serology has clear application in cluster randomised trials, particularly in settings where measuring clinical incidence or infection is less reliable due to seasonal fluctuations, limitations in health care seeking, or incomplete testing and reporting. Funding: This study was supported by Novartis Foundation (A122666), the Bill & Melinda Gates Foundation (OPP1160129), and the Horchow Family Fund (5, 300, 375, 400).